THU0632-HPR DETERMINANTS OF HAPPINESS AND QUALITY OF LIFE IN PEOPLE WITH SYSTEMIC SCLEROSIS: A STRUCTURAL EQUATION MODELLING APPROACH. (2nd June 2020) - Santiago, T.; Santos, E.; Duarte, A. C.; Martins, P.; Sousa, M.; Guimarães, F.; Azevedo, S.; Ferreira, R.; Guerra, M.; Cordeiro, A.; Cordeiro, I.; Pimenta, S.; et al.
Abstract : Background: In recent years more attention has been given to patients reported outcomes (PROs). Systemic sclerosis (SSc) is no exception. As there is no effective treatment or cure to SSc, it is important to recognize the relevance to patients of the different features of the disease to improve quality and enjoyment of life: the ultimate targets of therapy. Remarkably lacking in PROs is the evaluation of the overall perspective of subjective well being, equivalent to 'happiness' or "positive psychological dimensions". Objectives: To examine the determinants of happiness and quality of life (QoL) in patients with SSc with emphasis on disease activity, disease impact and personality traits. Methods: This is an observational, cross-sectional and multicenter study from six rheumatology clinics in Portugal. A total of 113 patients with SSc with a complete set of data on disease activity, disease impact, personality, quality of life and happiness were included. Structural equation modelling (latent variable structural model) was used to estimate the association between the variables using a maximum likelihood estimation with Satorra-Bentler's correction and performed with STATA® 15.0. Two hypotheses were pursued: H1 – Disease activity and impact of disease are negatively associated to overall QoL and happiness; H2 – 'Positive' personality traits are related to happiness both directly and indirectly through perceived disease impact. Results: Results obtained in the structural equation measurement model indicated a good fit [χ2/df=1.44; CFI=0.93; TLI=0.90; RMSEA=0.06] and supported all driving hypotheses (Figure 1 ). Happiness was positively related to 'positive' personality (β=0.45, p=0.01) and, to a lesser extent, negatively related with impact of disease (β=-0.32; p=0.01). This impact, in turn, was positively related to EUSTAR activity score (β=0.37; p<0.001) and mitigated by 'positive' personality traits (β=-0.57; p<0.001). Impact of disease had a much stronger relation with QoL than with happiness (β=-0.78, p<0.001). Quality of life and happiness had no statistically significant relationship. Conclusion: Optimization of Qol and happiness in people with SSc requires effective control of the disease process. Personality and its effects upon the patient´s perception of the disease impact, seems to play a pivotal mediating role in these relations and should deserve paramount attention if happiness and enjoyment of life is taken as the ultimate goal of health care. Disclosure of Interests: Tânia Santiago: None declared, Eduardo Santos: None declared, Ana Catarina Duarte: None declared, Patrícia Martins: None declared, Marlene Sousa: None declared, Franscisca Guimarães: None declared, Soraia Azevedo: None declared, Raquel Ferreira: None declared, Miguel Guerra: None declared, Ana Cordeiro Consultant of: Ana Cordeiro has acted as a consultant for Roche, Speakers bureau: Ana Cordeiro has received speaker fees from Boehringer Ingelheim, Lilly, and Vitoria, Inês Cordeiro: None declared, Sofia Pimenta: None declared, Patrícia Pinto: None declared, Maria Joao Salvador: None declared, José Antonio P. da Silva Grant/research support from: Pfizer, Abbvie, Consultant of: Pfizer, AbbVie, Roche, Lilly, Novartis